TUBEKTOMI DI TENGAH MASYARAKAT: PENDEKATAN KEPERAWATAN KOMUNITAS DALAM HUKUM ISLAM - Salsa Nazala Salsabil; Iskandar, Tasya Cesarina; Saputra, Syahla' Khairiyah; Rustandi, Kayla Salma Nazarra; Dian Novia; Tedi Supriyadi; Akhmad Faozi (Universitas Mathla’ul Anwar Banten, 2025)
Tubectomy, as a permanent contraceptive method, triggers ethical and religious dilemmas in society, especially in the context of Islam which emphasizes the importance of community regeneration. This study aims to explore the perspective of Islamic law and the views of community nursing on tubectomy, as well as to examine the medical and social factors that influence decision making. This study uses a qualitative approach with a phenomenological method and a case study design. Involving four participants from various backgrounds, namely two scholars, one community health nurse, one patient who has undergone a tubectomy procedure, all sources domiciled in Sumedang. Data were collected through offline interviews, then the results of the interviews were processed through various stages starting from collecting data from all interview sources and relevant journals, managing data by checking the accuracy of the data, interpreting data, and drawing conclusions. The results of the study indicate that there are various factors that cause tubectomy to become one of the contraceptive methods used, this is influenced by the number of children, health factors, economic factors, and career priorities. The perspective of scholars highlights that tubectomy is contrary to Islamic teachings because of its nature which causes infertility, and changes human nature. If used for birth control, it is forbidden unless it is used for reasons that are in accordance with sharia. Meanwhile, the findings also show the important role of community nurses as educators who bridge medical understanding and religious values in society. Formal and participatory education involving religious and community leaders has proven effective in increasing acceptance of this procedure. This study concludes that tubectomy is ethically and religiously acceptable if carried out within the framework of sharia, with appropriate health and educational considerations.